2014
DOI: 10.1039/c4cp02135e
|View full text |Cite
|
Sign up to set email alerts
|

Ligand/cluster/support catalytic complexes in heterogeneous ultrananocatalysis: NO oxidation on Ag3/MgO(100)

Abstract: In the present work we explore via first-principles simulations whether the ligand/cluster/support catalytic complex generated by CO oxidation over silver trimers deposited on the regular MgO (100) surface -i.e. a Ag 3 /carbonate or Ag 3 (CO 3 )/MgO(100) species -can be used as a catalyst in a different reaction: the selective oxidation of NO to NO 2 (or NOox). The Ag 3 (CO 3 )/MgO(100) complex is first shown to be reasonably stable at room temperature in terms of both disaggregation and sintering, and that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Alumina-supported silver nanoparticles of a few tens nanometer in size are typically used in the industrial context, 78,79 but the reaction can be conducted efficiently also over subnanometer cluster catalysts, as in our previous studies on Ag 3 cluster catalysts supported on the MgO(100) regular surface. 39,40,80 As discussed in detail in section 2, here we focus exclusively on the rate-determining step of the EtOx mechanism on Ag 3 (CO 3 )(C 2 H 4 ), i.e., the step:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alumina-supported silver nanoparticles of a few tens nanometer in size are typically used in the industrial context, 78,79 but the reaction can be conducted efficiently also over subnanometer cluster catalysts, as in our previous studies on Ag 3 cluster catalysts supported on the MgO(100) regular surface. 39,40,80 As discussed in detail in section 2, here we focus exclusively on the rate-determining step of the EtOx mechanism on Ag 3 (CO 3 )(C 2 H 4 ), i.e., the step:…”
Section: Resultsmentioning
confidence: 99%
“…the barriers for the other steps being sufficiently low that the population of the corresponding intermediates can be considered as negligible) and we modify the catalyst of our original study 39 in two different ways, studying (i) Ag 3 (HCO 3 )(C 2 H 4 ) 2 (O) and (ii) Ag 3 (CO 2 F)(C 2 H 4 ) 2 (O) aggregates supported on the regular MgO(100) surface, and possibly how they might realize the conclusive catalytic step and evolve the C 2 H 4 O molecule as a photoassisted process. Moreover, since this "Ag 3 (XCO x )-(C 2 H 4 ) 2 (O) → Ag 3 (XCO x )(C 2 H 4 ) + C 2 H 4 O" step can actually be realized either as a single-step process or as a two-step process in which (1) the aggregate first rearranges to an oxametallocycle species to allow for oxygen-adatom migration from one C 2 H 4 to the other, followed by (2) the detachment of the C 2 H 4 O epoxide molecule and its evolution into the gas phase, in the case of Ag 3 (CO 2 F)(C 2 H 4 ) 2 (O) we calculated both the initial configuration and its isomeric oxametallocycle variant with the migrated O-adatom.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational methods can explore intermediates and transition energy states that otherwise may be ignored in experimental studies. Theoretical simulation analysis of the different catalytic aspects (size, support, composition, intermediate reagents and products) in relation to the catalytic activity has been evaluated for different reactions involving AgNPs [36][37][38][39]. DFT is a widespread method, which can help us to understand the stability and electronic properties of nanoparticles, their adsorption modes on support surfaces, and to elucidate mechanisms and reaction rates for different reactions taking place on the catalyst surface, which together with experimental studies would allow the development of new catalysts, more efficient and in a more rational way [40].…”
Section: Introductionmentioning
confidence: 99%
“…The mapping of the potential energy surface indicated that monomer diffusion at room temperature is unlikely on both supports. Sementa et al [22] found that the intermediate carbonate species Ag 3 (CO 3 ) formed on the MgO(1 0 0) surface during the oxidation of CO on supported silver trimers and is probably the actual catalyst. They also investigated whether such a species may be the catalyst for various other reactions.…”
Section: Introductionmentioning
confidence: 99%